Gangguan Serebellar pada Pasien Berusia 55 Tahun dengan Multiple System Atrophy - Maulidia, Agnes Annurul (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Multiple system atrophy is a progressive neurodegenerative disease clinically characterized by autonomic failure (urogenital, cardiovascular or both), ataxia and parkinsonism in any combination (Sidoroff). MSA is classified into Parkinsonism (MSA-P) and Cerebellar (MSA-C) sub-types. Determining the correct diagnosis for multiple system atrophy remains a challenge in daily clinical practice as a comprehensive examination is required. Few journals discuss the diagnosis and management of multiple system atrophy thoroughly. Case: A 55-year-old man came to the neurology clinic with complaints of frequent falls accompanied by typical cerebellar symptoms. Neurologic examination revealed impaired cerebellar function. MRI examination of the head with contrast showed a typical picture of cerebellar type multiple system atrophy. Conclusion: Rapid diagnosis and adequate multidisciplinary treatment are needed to prevent aggravation of multiple system atrophy symptoms. Symptomatic and supportive therapy is needed to improve the patient's quality of life.